Interpersonal style controller and perception of competence in higher education (European Journal of Education and Psychology, 2018)
The aim of this study was to create and validate the Scale of Style Controller and check its relationship with perceived competence of students in higher education. For this purpose a sample of 276 Spanish university students with a mean age of 22 years who were measured style controller and basic psychological need of academic competence was used. The results of confirmatory factor analysis, internal consistency and temporal stability were adequate. The controller style was not related to perceived competence. This study has enabled to provide a valid and reliable scale that can be used to measure interpersonal style controller type of teaching in higher education.